STRATEGI DINAS PENDIDIKAN DALAM MENINGKATKAN MUTU PENDIDIKAN SEKOLAH LUAR BIASA DI KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Ningrum, Tri Ayu; Rusli SD, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
One of the problems faced by the Indonesian nation is the unequal society gets education. Our country is established precisely to educate the sons and daughters of the nation, in order to live worthy human dignity in addition to other nations in the world. The nation's intelligence is done primarily through educational efforts. Special School (SLB) is a formal educational institution that serves education for children with special needs. As an educational institution SLB is formed by many elements that are directed to achieve educational goals, the core process is learning for learners. So the SLB is a special educational institution that organizes educational programs for children with special needs.This study aims to determine the Strategy of the Department of Education in Improving utu Education Special School in Tenayan Raya District Pekanbaru City. The concept of theory that researchers use is the concept of strategy by using SWOT analysis theory. The research method used is qualitative research. In the data collection, researchers used interview techniques, observations, and documentation set based on Snowball Sampling.From the results of the study showed that the Strategy of the Department of Education in Improving the Quality of Special School Education in Tenayan Raya of Pekanbaru not yet optimal. This can be seen from the weak utilization of the strengths possessed by the Education Department of Riau Province such as less optimal implementation of training and socialization provided for educators. And also has not been able to maximize the opportunities that are owned by the Education Department of Riau Province such as accountability to the development of the SLB as a primary container to help Special Children with Ability.Keyword : Strategy, Quality of School Education Extraordinary